EL IMPACTO AMBIENTAL DEL CRECIMIENTO ESPACIAL DE LA CIUDAD DE CORRIENTES SOBRE LAGUNAS PERIURBANAS - Felix I. contreras (Boletín Geográfico)
Corrientes City is limited by natural features that prevent its expansion towards the north and west; while toward the south and east, the landscape is seriously affected by periodical floods owing to the presence of “bañados” and “cañadas”. The Lomada Norte is an excellent growing area and constitutes a “source of attraction” to buildings policyspeculation that is manifested in the great demand of occupation of such space. This sandy landscape is characterized by the presence of shallow lakes, which are mostly small, with small depth and with scarce water retention capacity. In this sense, our objective is to demonstrate the impact of the boundaries expansion of the city on the existence and permanence of the shallow lakes near Corrientes city. Thus, aiming to detect changes in the cover of the terrain and their impact on the landscape, satellite images, which allow the analysis of recent changes and, aerial photographs of Corrientes city took in 1950, were analyzed and compared by using GIS methods. The results obtained revealed that, from 1950 to date, 51 shallow lakes have disappeared as a consequence of the spatial expansion of the city, exclusively. Moreover, the analysis of the satellite images also showed that, after a long dried period, the areas previously occupied by shallow lakes were occupied by human settles. It is concluded that the occupation of new areas impact directly on the landscape, being of fundamental importance to implement land development policies to regulate and control the advance of the city frontier, particularly when vulnerable landscapes are affected exposing population to certain risks.